2009
DOI: 10.1021/nl9020717
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic GaAs/GaMnAs Core−Shell Nanowires Grown by Molecular Beam Epitaxy

Abstract: GaAs/GaMnAs core-shell nanowires were grown by molecular beam epitaxy. The core GaAs nanowires were synthesized under typical nanowire growth conditions using gold as catalyst. For the GaMnAs shell the temperature was drastically reduced to achieve low-temperature growth conditions known to be crucial for high-quality GaMnAs. The GaMnAs shell grows epitaxially on the side facets of the core GaAs nanowires. A ferromagnetic transition temperature of 20 K is obtained. Magnetic anisotropy studies indicate a magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
90
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 52 publications
1
90
0
1
Order By: Relevance
“…For example, the formation of ferromagnetic precipitates or clusters such as MnAs should be considered as a possible source of magnetism. 11,16,17 Recently, core-shell structured NWs consisting of GaAs/GaMnAs, 18 GaAs/MnAs, 19,20 and InGaAs/GaMnAs 21 have been considered as well. Some of these studies showed that low temperature grown GaMnAs shells can contain high Mn concentrations up to $5% and have ferromagnetic phase transitions above 20 K. 18,21 We have demonstrated previously 11,13 that it is possible to grow GaMnAs NWs by MBE at low temperatures (300-350 C) and if the growth temperature is slightly too high, the formation of MnAs nanoclusters occurs on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the formation of ferromagnetic precipitates or clusters such as MnAs should be considered as a possible source of magnetism. 11,16,17 Recently, core-shell structured NWs consisting of GaAs/GaMnAs, 18 GaAs/MnAs, 19,20 and InGaAs/GaMnAs 21 have been considered as well. Some of these studies showed that low temperature grown GaMnAs shells can contain high Mn concentrations up to $5% and have ferromagnetic phase transitions above 20 K. 18,21 We have demonstrated previously 11,13 that it is possible to grow GaMnAs NWs by MBE at low temperatures (300-350 C) and if the growth temperature is slightly too high, the formation of MnAs nanoclusters occurs on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…11,16,17 Recently, core-shell structured NWs consisting of GaAs/GaMnAs, 18 GaAs/MnAs, 19,20 and InGaAs/GaMnAs 21 have been considered as well. Some of these studies showed that low temperature grown GaMnAs shells can contain high Mn concentrations up to $5% and have ferromagnetic phase transitions above 20 K. 18,21 We have demonstrated previously 11,13 that it is possible to grow GaMnAs NWs by MBE at low temperatures (300-350 C) and if the growth temperature is slightly too high, the formation of MnAs nanoclusters occurs on the surface. However, due to high disorder in terms of NW orientation, crystallographic defects, and morphology, other growth regimes of Mn-doped GaAs NWs have been exploited: (i) Ga catalyzed NWs grown at high temperature on Si(100), 13 (ii) Ga catalyzed NWs grown at high temperature on Si(111), 22 and (iii) low-temperature grown GaMnAs shells on high-temperature grown Au-catalyzed GaAs NWs on GaAs(111)B.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] To fabricate SFCSNws, commonly first semiconductor Nws are fabricated by epitaxial methods such as molecular beam epitaxy or metal oxide chemical vapor deposition and are in a second growth step coated with the ferromagnetic material. Thereby the magnetic material does not necessarily stick to the Nw shells exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the insight of ensemble measurements on the Nws themselves that were reported recently by using superconducting quantum interference device magnetometry (SQUID), small angle neutron scattering and ferromagnetic resonance techniques are quite equivocal. [1][2][3][4][5][6][7] Single Nw magnetic investigation on the other hand gives precise information about only the selected structure (one Nw shell) but thus it reflects only the information obtained from one single event of measurement (from one Nw). To draw conclusions from such measurements over all other Nws is hence quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The cylindrical shape of the ferromagnet in such core/shell NWs causes a magnetization along the wire axis, i.e. perpendicular to the substrate surface.…”
Section: Introductionmentioning
confidence: 99%